Utilizing neutronics modelling to predict changing Pu ratios in UO2 in the presence of Th. (July 2021) - Evitts, L.J.; Gilbert, M.R.; Middleburgh, S.C.; Lee, W.E.; Dahlfors, M.
Abstract: The isotopic fractions of plutonium produced in a reactor are of significant value as nuclear forensic signatures, and the mechanisms of their production and alteration should be investigated thoroughly. A series of neutronics calculations were made on a typical UO2 PWR setup, introducing (Th, U)O2 MOX rods gradually, to investigate how the presence of Th affects the 240 Pu/ 239 Pu and 242 Pu/ 239 Pu ratios in the remaining UO2 fuel rods. A relationship is found that links the percentage change in these ratios, with the burnup and Th content in the configuration. In an extreme case, it was found that the presence of Th may increase the ratio of 242 Pu/ 239 Pu by as much as 3.5% at low burnup. Highlights: Historically, the isotopic fraction of plutonium may be used as a fingerprint of the reactor type. Homogeneous thorium-based fuels have an unknown divergence from known fingerprints. A fingerprint is derived from neutronics calculations based on thorium content.